Eratosthenes’ map of the oecumene - Viktoras Lukoševičius; Tomas Duksa (Geodesy and Cartography, 2012)
Eratosthenes (circa 276 B.C.–194 B.C.) is considered a famous scientist of ancient Greece. He was a mathematician and geographer. Born in Cyrene, now Shahhat (Libya), he was appointed to teach the son of the Egyptian King Ptolemy III Euergetes. In 240 B.C., he became the third chief librarian the Great Library of Alexandria. Eratosthenes laid basics for mathematical geography. He was the first to calculate precisely in an original way the Earth meridian's length between Syene and Alexandria. For this purpose he used perpendicular projection of the sun rays during summer solstice (06.22) near the town Syene, now Aswan. His estimation of the length of the Earth's radius (6300 km) is close to present estimation (6371 km). He calculated that a year possesses 365.25 days. He also emphasized the significance of maps as the most important thing in geography. Eratosthenes was the first one to use the term “geographem” to describe the Earth. In this way he legitimized the term of geography. He also put into system geographical information from various sources in order to obtain a map of the world as precise as possible.